2006
DOI: 10.1021/la053464p
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of Vesicles and Dispersed Cubic and Hexagonal Particles in Amino Acid-Based Catanionic Surfactant Systems

Abstract: Mixed catanionic surfactant systems based on amino acids were investigated with respect to the formation of liquid crystal dispersions and the stability of the dispersions. The surfactants used were arginine-N-lauroyl amide dihydrochloride (ALA) and N R -lauroyl-arginine-methyl ester hydrochloride (LAM), which are arginine-based cationic surfactants; sodium hydrogenated tallow glutamate (HS), a glutamic-based anionic surfactant; and the anionic surfactants sodium octyl sulfate (SOS) and sodium cetyl sulfate (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 68 publications
0
54
0
Order By: Relevance
“…This surfactant system was characterized elsewhere [34]. It was found that it, in analogy with several other mixed cationic-anionic surfactant systems, presents a spontaneous formation of vesicles having a long-term stability; in fact they remain over our extended times of investigation suggesting that they may be thermodynamically stable.…”
Section: Dna Addition To the Vesicle Systemmentioning
confidence: 92%
“…This surfactant system was characterized elsewhere [34]. It was found that it, in analogy with several other mixed cationic-anionic surfactant systems, presents a spontaneous formation of vesicles having a long-term stability; in fact they remain over our extended times of investigation suggesting that they may be thermodynamically stable.…”
Section: Dna Addition To the Vesicle Systemmentioning
confidence: 92%
“…21 Furthermore, ions of biological origin, such as choline and alkaline amino acids (lysine and arginine), have been used as counter-ions to disperse fatty acids because they exist in aqueous solution with different ionic states such as anionic, cationic and amphoteric, due to the amino groups and carboxyl groups. [22][23][24] The self-assembled structures formed by these two kinds of biomaterials can greatly increase the solubility of fatty acids in aqueous solution by decreasing the Kra point; 16,25 on the other hand, the ion of biological origin itself provides a benecial effect for biomedical applications.…”
Section: 15mentioning
confidence: 99%
“…2,[6][7][8]20 In particular, the phase transitions involving cubic mesophase formation by surfactants and lipids exhibit considerable complexity. [21][22][23][24][25][26][27][28][29][30][31][32][33] They have attracted growing interest 34 and have provoked investigations focusing on their analogy with the mesophase transitions in di-and triblock copolymers forming LC structures.…”
Section: -12mentioning
confidence: 99%